PERBANDINGAN MODEL OPSI BLACKSCHOLES DAN MODEL OPSI GARCH DI BURSA EFEK INDONESIA - Riko Hendrawan (Jurnal Keuangan dan Perbankan, 2010)
The purpose of this research was to compare the accuracy of Black-Scholes Opt ionModel and GARCH opt ion models for Stock opt ion ut ilizing data f rom Ast ra, BCA, Indofoodand Telkom at the Indonesian Stock Exchange. The intraday stock return of Astra, BCA, Indofoodand Telkom exhibited an overwhelming presence of volat ilit y cluster, suggesting that GARCHmodel had an ef fect which best corresponded with the actual price. The best model wasconst ructed using ARIMA model and the best lag in GARCH model was ext racted. The findingf rom this research showed that by comparing the average percentage mean squared errors ofthe GARCH Opt ion Model and the Black-Scholes Opt ion Model, the former was found moreaccurate than the lat ter. GARCH Model relat ively improved average percentage mean squarederrors of Black-Scholes Model; one month opt ion showed a twent y eight point ten percentimprovement , two month option showed twenty three point thirt y percent and three monthopt ion showed twent y percent .